Effects of clostridium butyricum and bifidobacterium on BTLA expression on CD4+ T cells and lymphocyte differentiation in late preterm infants. (November 2016) - Zhang, Shi-Fa; Tang, Zong-Sheng; Tong, Ling; Tao, Xiang-Xiang; Suo, Qi-Feng; Xu, Xue-Mei
Abstract: Background & aims: Probiotics is recognized to promote growth performance and immune function via balancing the intestinal microflora. Live clostridium butyricum and bifidobacterium combined powder (LCBBCP) has been widely to treat intestinal dysbacteriosis in newborns in China. This study was undertaken to investigate the effects of the combined probiotics on the expression of B and T lymphocyte attenuator (BTLA) on CD4 + T cells and the differentiation of lymphocyte subsets in late preterm infants. Methods: Eighty eligible late preterm infants were equally randomized into LCBBCP therapy group (oral LCBBCP dissolved in formula milk before intake) and control group (treated with simple formula milk for preterm infants) by random digit table. Flow cytometry was used to determine the expression level of BTLA on CD4 + T cells and the percentage of individual subpopulation of lymphocytes in peripheral-blood mononuclear cells (PBMCs) obtained from the late preterm infants in both groups. Results: BTLA protein expression on CD4 + T cells showed no significant change in LCBBCP therapy group before and after intervention, yet was rapidly and significantly down-regulated in the controls. The percentage of increased CD4 + T cells, decreased CD8 + T cells and increased ratio of CD4 + /CD8 + T cell proportion were seen in both groups after treatment, yet the increasing or decreasing extent in LCBBCP therapy group was more obvious than in control group. The proportion of NK cells and B lymphocytes remained no significant difference between the two groups before and after therapy. Conclusions: LCBBCP appears capable of facilitating the activation, proliferation and differentiation of T lymphocytes, which is beneficial to improving immunity in late preterm infants. The continuous high expression of BTLA on CD4 + T cells in LCBBCP therapy group may be involved in the inhibiting of excessive activation of T lymphocytes. Our findings may lay a basis for further clinical evaluation of the efficacies and wider clinical recommendation of probiotics containing live clostridium butyricum and bifidobacterium for late preterm infants. Highlights: LCBBCP promotes the continuous high expression of BTLA on CD4 + T cells. LCBBCP facilitates the activation, proliferation and differentiation of T cells. LCBBCP is beneficial to the improvement of immunity in late preterm infants.